Denmark's Master of Public Governance program: Assessment and lessons learned. Issue 1 (March 2017) - Greve, Carsten; Pedersen, Anne Reff
This paper focuses on Denmark's Master of Public Governance and its assessments and lessons learned. Denmark is seen to have an efficient economy and public sector, a digitalized public service delivery system, and an advanced work–life balance. The Danish government invested substantial resources into developing a Master of Public Governance program – a flexible and modular program for public managers to take over a period of up to six years. The paper focuses on the Copenhagen version of the Master of Public Governance program. More than 1000 public managers from central, regional and local government are now active in pursuing an executive public management education through this program. The development, structure, content and the innovative teaching ideas are presented. The available data, including an official evaluation of the MPG program, is used to assess the program and present some lessons learned. The program has achieved its goals as public managers express satisfaction with the content and the flexible structure of the program, which suited more governance-oriented public managers with a need for strategic-thinking public managers, and has provided them with an opportunity to try out innovative teaching ideas. Lessons learned include the necessity of securing back-up from the government for a program of this considerable size, offering a flexible array of accessible and up-to-date courses and ensuring collaboration between universities offering the program.